Differences between neonatal units with high and low rates of breast milk feeding for very preterm babies at discharge: a qualitative study of staff experiences - Jenny McLeish; Annie Aloysius; Chris Gale; Maria Quigley; Jennifer J. Kurinczuk; Fiona Alderdice (BMC Pregnancy and Childbirth)
Abstract Background Breast milk has significant benefits for preterm babies, but ‘very preterm’ babies are unable to feed directly from the breast at birth. Their mothers have to initiate and sustain lactation through expressing milk for tube feeding until their babies are developmentally ready to feed orally. There are wide disparities between neonatal units in England in rates of breast milk feeding at discharge. This study explored health professionals’ experiences of barriers and facilitators to their role in supporting breast milk feeding and breastfeeding for very preterm babies. Methods 12 health professionals were interviewed, from four neonatal units in England with high or low rates of breast milk feeding at discharge. Interviews were analysed using comparative thematic analysis. Results Five themes were developed: ‘The role of the infant feeding specialist’, ‘Achieving a whole team approach to breast milk feeding’, ‘Supporting initiation of breastfeeding’ ‘Supporting long-term expressing’, ‘Supporting the transition to breastfeeding’. There were notable differences between neonatal units in the time allocated to specialist feeding support, the team’s sense of collective responsibility for supporting feeding, leadership, the use of external standards as levers for change, and training for the multi-disciplinary team. The feeding challenges faced by mothers of very preterm babies could be made worse where there was no joined-up working between neonatal and postnatal staff; inadequate facilities for mothers to stay with their babies; and when opportunities were missed to give information about the importance of early initiation of expressing and to support mothers’ confidence during the transition to direct breastfeeding. Conclusions Effective support can be influenced by having a supernumerary post dedicated to infant feeding; strong leadership that champions breast milk feeding and breastfeeding within Family Integrated Care; maintaining accountability by using existing quality improvement tools and accredited standards for neonatal units; and training for the whole multi-disciplinary team that encourages and enables every member of staff to take an appropriate share of responsibility for consistently informing and assisting mothers with expressing and breastfeeding. Joined-up working between staff on antenatal and postnatal wards and neonatal units is important to enable integrated feeding support for the mother-baby dyad.